Development Of A Patient Control And Monitor System Using Esp32-Cam And Android - Suwarmiyati, Suwarmiyati (Jurnal Teknologi Elekterika, 2024)
Health is an inalienable area of human life. Therefore, developments need to be made so that in the field of health can support human life in this era. The DEVELOPMENT OF CONTROL SYSTEMS AND MONITORING PAT development could be the development of a medical aid tool that greatly supports the performance of the medical staff.To change the settings and modes of the patient monitor in the room of isolation, it would be quite risky for doctors and nurses if they had to enter the isolation compartment at all times if only to see the patient's condition in a patient monitor device.The author intends to design a tool to make it easier for the doctor and nurse in controlling the patient condition with ESP32 based CAM WIRELLES, in this discussion the author uses ARDUINO UNO, BLUETOOTH MODUL HC-05, and the application Monitoring Patient Monitor.After testing, this device displays images with 2 MEGAPIXEL quality and the range power of the BLUETOOTH HC-05 Module so that the device is usable and suitable for testing. And the range power (connection distance/application on the device) is 1 – 8meters.